Controle postural de crianças com paralisia cerebral na postura sentada durante diferentes tarefas na equoterapia - Flores, Fabiana Moraes (2018)
Postural control can be defined as the ability to control the body’s position in space for the purposes of stability and orientation. This complex ability is commonly deficient in children with cerebral palsy (CP). However, rehabilitation methods can produce considerable improvements in this ability, including Hippotherapy. During a session of Hippotherapy the repetitive patterns of movement made by the horse are used for the purposes of stimulation of postural control and can be altered by means of modifications of this task. In this context, the evaluation of the dynamic parameters of the center of pressure (COP) on the contact surface between rider and horse becomes important to elucidate the responses in the rider's postural control. Therefore, the aim of this study was to verify if the postural control of children with CP is modified when variations in the types of surfaces and in the speed of the horse's walking are realized in Hippotherapy’s sessions. Eight children diagnosed with bilateral spastic CP (GCP) practicing equine therapy and eight children with typical development (GDT) matched for age and gender participated in this study. All the children were evaluated in static baseline and dynamics during horse riding with different tasks varying surfaces, as sand and asphalt and the speed, as slow and fast. The evaluations of children with CP occurred for one week of washout between them to avoid modulation of tone and / or fatigue and in the GDT were performed only one day. The amplitude (ACOP) and velocity of COP (VelCOP) displacement in the anteroposterior and mediolateral directions were determined by a portable pressure measurement system positioned on the saddle. The four possible combinations between surfaces and speeds were evaluated. The results indicate GPC and GDT present higher ACOP and VelCOP values in the evaluated dynamic situations than in the static ones. In dynamic situations GPC presented ACOP and VelCOP values higher than GDT. The type surface on which the horse is lead produces changes in the ACOP in mediolateral direction of the children and in the fast speed all parameters of the COP have been shown to be higher. The responses of the postural control of the children with CP during Hippotherapy’s sessions suffered variations regarding ACOP when surface was modified and in the ACOP and VelCOP as a consequence of the increase of the horses’ speed. The results reinforce the importance of increase the horses’ speed as a strategy to higher demand for postural control of children with CP to be used in the sessions of Hippotherapy.